Korelasi Antara Ukuran Tubuh dan Karakteristik Ambing Terhadap Produksi Susu Kambing Saanen di Daerah Tropis - Elly Albert Ardiansyah; Yustina Yuni Suranindyah; Dyah Maharani; Muhammad Arif Darmawan (Sekolah Vokasi, Universitas Sebelas Maret, 2022)
The aim of this research was to determine the correlation between udder and body size of Saanen goats on milk production in BBPTU-HPT Baturraden. Total of 61 lactating Saanen goats were used in this study. The size of the udder was measured including the width and length of the udder, the inner and outer circusmference of the udder, the shape and volume of the udder, the length, circumference and direction of the nipple. Body measurements were measured including chest circumference, ear length and width, and body length and height. Body and udder characteristics were assessed once before milking while milk production was measured each milking. Data were analyzed using regression analysis. The correlation between body length, chest circumference, height, ear length, ear width, and neck wattle with milk production were 1.0%, 0.0%, 4.1%, 5.1%, 2.1 %, and 0.0% respectively. The correlation between udder volume, udder outer circumference, udder inner circumference, udder width, udder length, nipple circumference, and nipple length with milk production were 54.5%, 49.4%, 41.4%, 55.9,%, 10.9%, 24.2%, and 28.4% respectively. Saanen goat milk production had a correlation with udder characteristics but had no correlation with body size.